2014
DOI: 10.1021/es501811k
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Concentrations of Maternal Poly- and Perfluoroalkyl Substances over the Course of Pregnancy and Predictors of Exposure in a Multiethnic Cohort of Cincinnati, Ohio Pregnant Women during 2003–2006

Abstract: Data on predictors of gestational exposure to poly- and perfluoroalkyl substances (PFASs) in the United States are limited. To fill in this gap, in a multiethnic cohort of Ohio pregnant women recruited in 2003–2006, we measured perfluorooctanesulfonate (PFOS), perfluorooctanoate (PFOA), and six additional PFASs in maternal serum at ∼16 weeks gestation (N = 182) and delivery (N = 78), and in umbilical cord serum (N = 202). We used linear regression to examine associations between maternal serum PFASs concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
178
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(216 citation statements)
references
References 70 publications
29
178
3
Order By: Relevance
“…In the early 1990's when the ALSPAC prenatal blood collection took place, one important source of PFC exposure is thought to have occurred through contact with new furnishings and carpets in home and office settings; thus, participants of higher socioeconomic status might have experienced the highest exposures. Interestingly, concentrations of maternal PFCs in this data tend be positively associated with educational status (23)(24)(25). In this data, daughters of less educated (lower socioeconomic status) moms may have experienced more complex dynamic combinations of environmental, lifestyle and social stressors over time (20).…”
Section: Discussionmentioning
confidence: 60%
“…In the early 1990's when the ALSPAC prenatal blood collection took place, one important source of PFC exposure is thought to have occurred through contact with new furnishings and carpets in home and office settings; thus, participants of higher socioeconomic status might have experienced the highest exposures. Interestingly, concentrations of maternal PFCs in this data tend be positively associated with educational status (23)(24)(25). In this data, daughters of less educated (lower socioeconomic status) moms may have experienced more complex dynamic combinations of environmental, lifestyle and social stressors over time (20).…”
Section: Discussionmentioning
confidence: 60%
“…Isotope-labeled internal standards for quantification included: 13 C 2 -PFOA, 13 C 4 -PFOS, 18 O 2 -PFHxS, 13 C 5 -PFNA, and 13 C 2 -PFDeA. Calibration standards were spiked into calf serum to account for potential matrix effects (Kato et al, 2014). The LODs were 0.082 ng/mL (PFNA), 0.1 ng/mL (PFOA, PFHxS, PFDeA), and 0.2 ng/mL (PFOS).…”
Section: Methodsmentioning
confidence: 99%
“…Each analytic batch included reagent blanks and low-concentration and high-concentration quality control (QC) materials, prepared from a calf serum pool. The coefficients of variation of repeated measurements of the QC materials were ~6% (Kato et al, 2014). Concentrations were averaged among women who had >1 sample to obtain a measure of prenatal PFASs for PFOA, PFOS, PFHxS, PFNA, and PFDeA (in ng/mL), resulting in a total of 242 women with either an averaged concentration of prenatal PFASs or a measurement at 16 or 26 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with our findings, Apelberg et al (2007) reported that the multiparous births group has lower PFOA concentrations than primiparous births (p = 0.02) in 299 cord blood samples from the Baltimore THREE Study in -2005 also indicated a correlation between parity and cord PFOA levels among 70 South Koreans (OR = 0.32, 95% CI 0.1, 1.05). Many studies demonstrated a negative correlation between PFOA in maternal and parity (Goudarzi et al 2016;Kato et al 2014;Kishi et al 2015;Lee et al 2016), and concentrations of PFOA in cord serum were highly correlated with those in maternal serum Needham et al 2011). Perhaps these findings partly explain the difference of cord PFOA concentration due to parity.…”
Section: Isomeric Profile Of Pfoa In Cord Serummentioning
confidence: 97%